2019
DOI: 10.2298/ijgi1902109l
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of summer discomfort in Nis (Serbia) using Humidex

Abstract: The bioclimatic analysis of the central area of the city of Niš conducted in this paper is based on the use of the bioclimatic index Humidex, which represents subjective outdoor temperature that one feels in warm and humid environment. The purpose of this research is to observe the index change on a daily basis during the hottest part of the year (June, July, and August) over the period from 1998 to 2017. For the purposes of this analysis, hourly (7:00, 14:00), maximum and mean daily values of meteorological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…While studying the characteristics of the heat waves in central Serbia , Unkašević and Tošić (2011) detected an increase in heat wave duration in addition to an increase in heat wave frequency of occurrence during the period from 1999 to 2007. Moreover, based on the HWDI, heat waves at Novi Sad show a trend of increasing tropical days (t max ≥ 30.0 • C) from 1960 to 2010, indicating the years 1994, 1998, 2000, 2003, 2009(Malinović-Milićević, 2013.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While studying the characteristics of the heat waves in central Serbia , Unkašević and Tošić (2011) detected an increase in heat wave duration in addition to an increase in heat wave frequency of occurrence during the period from 1999 to 2007. Moreover, based on the HWDI, heat waves at Novi Sad show a trend of increasing tropical days (t max ≥ 30.0 • C) from 1960 to 2010, indicating the years 1994, 1998, 2000, 2003, 2009(Malinović-Milićević, 2013.…”
Section: Discussionmentioning
confidence: 98%
“…The period under observation could be longer for the purposes of keeping track of the trend of extremes. This shortcoming was attenuated by referencing a more detailed review of previous studies on the trend of maximum temperatures in Serbia reported by Unkašević and Tošić (2009a, 2011, Drljača et al (2009), Malinović-Milićević (2013), andMalinović-Milićević et al (2016). Furthermore, complete hourly weather data are missing, and therefore they are not sufficient for a more detailed analysis of UTCI values, which might be used for healthcare purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novi Sad, Niš, Belgrade, Leskovac -Milicevic et al, 2013;Unkašević & Tošić, 2013, 2015Savić et al, 2014Savić et al, , 2018Stanojević et al, 2014a;2014b;Šećerov et al, 2015;Bajšanski et al, 2015;Milošević et al, 2015aMilošević et al, , 2015bMilošević et al, , 2016Milošević et al, , 2017aMilošević et al, , 2017bDjukic et al, 2016;Anđelković et al, 2016;Basarin et al, 2016Basarin et al, , 2018Bogdanović-Protić et al, 2016;Djekic et al, 2018aDjekic et al, , 2018bVučković et al, 2019, Lukić et al, 2019 Slovenia Ljubljana Vidrih & Medved, 2013;Fikfak et al, 2017;Pogačar et al, 2017Pogačar et al, , 2019aPogačar et al, , 2019bPerčič et al, 2018;Žiberna & Ivajnšič, 2018 Measurements and assessment of thermal comfort and other climatological events responsible for outdoor thermal comfort were also investigated. Kovács & Németh (2012) evaluated the differences and changes of the thermal comfort conditions in the last half century in Budapest based on the measurements of two meteorological stations located in different environments (LCZs).…”
Section: Serbiamentioning
confidence: 99%
“…First was bioclimatic assessment of weather condition of Banja Luka (Republic of Srpska) for recreational purposes conducted by Pecelj and others [14]. Recently, Lukić et al [15] investigated the bioclimatic conditions of the central part of Niš, based on the use of Humidex. The purpose of this research was to observe the index change on a daily basis during the hottest part of the year over the period from 1998 to 2017.…”
Section: Introductionmentioning
confidence: 99%